Health technology assessement of the fxed combination of insulin glargine 100 UI/ml and lixisenatide in the treatment intensifcation of diabetes mellitus type 2 - S. К. Zyryanov; I. N. Dyakov (Izdatelstvo OKI, 2019)
Fixed antidiabetic drugs' combinations have aim to improve of Diabetes Mellitus type 2 (DMT2) control as well as a safety treatment increasing. Soliqua SoloStar® is a new registered drug for control of fasting and prandial glucose levels, contained insulin glargine 100 UI/ml and lixisenatide. In the published non-direct comparison, it was more eﬀective for DMT2 control vs insulin glargine 100 UI/ml and lixisenatide separately, and daily insulin dose was less on 22 UI.Aim: To evaluate of Soliqua SoloStar® reasonability og inclusion from pharmacoeconomics point of view into the State program of the free medical Aid guarantees.Materials and methods: Retrospective comparative economic analysis based on the published data of new methodology treatment with Soliqua SoloStar® in compare with the current treatment methodology with usage of insulin glargine and lixisenatide separately. Common used methodology of clinical-economic analysis was used, and target group of patients was created based on the Federal Diabetes Register. Direct medical cost was defned as a cost of medications. Diﬀerentiation between direct medical cost for the proposed methodology and current practice of the separate usage of insulin glargine and lixisenatide was calculated. Discounting at 5 % annually used in the calculation of the three years time horizon. Te results of health technology assessment are confrmed by sensitivity analysis. Microsof Excel was used for calculation.Results: Calculation has been performed for two pens of Soliqua SoloStar® with diﬀerent prices (Variation 1 and 2) in compare with diﬀerent drugs of insulin glargine 100 UI/ml and lixisenatide. Soliqua SoloStar® had less daily dose (by insulin glargine) on 22 UI vs free combination, and dose of lixisenatide was 20 mkg per day. Amount of patients who have reached HbA1c<7 % was higher in Soliqua group vs free combination group on 29 % (95 % CI: 20.2-30.7; p<0.0001). Cost of daily dose in Variation 1 is 269.72 RUR., for Variation 2 - 214.28 RUR. In the same time cost of the free combination of insulin glargine 100 UI and lixisenatide is depended from trade's name of the drug, while cost of lixisenatide per day is the same for free combination and has 158.8 RUR. Soliqua SoloStar® usage can decrease budget impact in comparison with free combination on 10.46-35.02 % (depending on cost of insulin glargine 100 UI from diﬀerent manufacturers and Soliqua pen cost). Cost-eﬀectiveness analysis has shown that Soliqua SoloStar® had economic advantages in compare with free components' combination on 51.95-65.08 % (depending on cost of insulin glargine 100 UI from diﬀerent manufacturers and variations of Soliqua pen cost).Conclusion: Soliqua SoloStar® has pharmacoeconomics evidences to be included into the Governmental program of free medical Aid in Diabetes Mellitus type 2.